Grandeur et décadence des femmes peintres entre la fin de la monarchie et la première moitié du XIXe siècle - Vera de Ladoucette (Les Cahiers de l'École du Louvre)
Based on a quantitative and qualitative study, this article aims to demonstrate the importance of the self-portrait to woman artists, which was a passport to the Salon in the eighteenth century, then observe the gradual diminution of their role, highlighted by a radical transformation in the way they represented themselves. For women on the eve of the French Revolution, the self-portrait “à la peinture” was a genuine artistic and political statement. The socioeconomic context changed in the early nineteenth century as bourgeois values confined women, whose only vocation became motherhood. Two representations of Adélaïde Labille-Guiard, twenty-three years apart – her Self-Portrait with Two Pupils from 1785 and the Painting Representing the Late Madame Vincent, Pupil of Her Husband by Marie-Gabrielle Capet – sum up this change. Henceforth, women limited their ambitions to the field of self-portraits. For the most part, they no longer represented the artist, just the woman.